Pengaruh Audit Lag, Leverage, dan Debt Default terhadap Opini Audit Going Concern - Yani Suryani, Lani Melani; Wawo, Andi; Anwar, Puspita Hardianti (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to examine the influence of audit lag, leverage, and debt default on going concern audit opinions on energy companies listed on the Indonesia Stock Exchange in 2019-2022. This research in quantitative research and data used in secondary data in the form of financial reports of energy companies for the 2019-2022 period which were accessed via the website www.idx.co.id using a purposive sampling method and a sample of 55 companies was obtained. Data analysis used logistic regression analysis. The results of this research show that audit lag has an effect on going concern, while leverage and debt default have no effect on going concern. This research has implications for several considerations, auditors need to be aware of the company’s going concern potential and take a more comprehensive approach in assessing going concern risk. Investors consider other factors besides leverage and debt default when considering investments risks